Knufia obscura sp. nov. and Knufia victoriae sp. nov., two new species from extreme environments. Issue 10 (6th October 2022) - Isola, Daniela; Prigione, Valeria Paola; Zucconi, Laura; Varese, Giovanna Cristina; Poli, Anna; Turchetti, Benedetta; Canini, Fabiana
Abstract : Six strains of black meristematic fungi were isolated from Antarctic soils, gasoline car tanks and from the marine alga Flabellia petiolata . These fungi were characterized by morphological, physiological and phylogenetic analyses. According to the maximum-likelihood analysis reconstructed with ITS and LSU sequences, these strains belonged to the genus Knufia. Knufia obscura sp. nov. (holotype CBS 148926) and Knufia victoriae sp. nov. (holotype CBS 149015) are proposed as two novel species and descriptions of their morphological, physiological and phylogenetic features are presented. Based on the maximum-likelihood analyses, K. obscura was closely related to Knufia hypolithi (99 % bootstrap support), while K. victoriae clustered in the clade of Knufia cryptophialidica and Knufia perfecta (93 % bootstrap support). Knufia victoriae, recorded in Antarctic soil samples, had a psychrophilic behaviour, with optimal growth between 10 and 15 °C and no growth recorded at 20 °C. Knufia obscura, from a gasoline car tank and algae, displayed optimal growth between 20 and 25 °C and was more tolerant to salinity than K. victoriae .